2011
DOI: 10.5152/akd.2011.120
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation due to metronidazole administration

Abstract: değildir. Tahmin edileceği ve birçok çalışmada gösterildiği üzere hastalarda ki değişim, bu üç girişimin ortak ya da kümülatif etkisi, bu müdahalelerin birinin oluşturacağı etkiden daha büyük olacaktır (3-5).Koroner anjiyografinin durumsal anksiyeteyi arttıran bir durum olması, koroner arter hastalığı tanısı alan hastaları eğitilmeye hazır hale getirmesi, çalışmamızda göz ardı edilen bir durum değildir. Kaldı ki, orta düzeyli anksiyetenin eğitime hazırlayıcı, yüksek düzeydeki anksiyetenin ise eğitimin etkisini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Stevens et al [24] demonstrated that the drugs were more active in the management of clostridial infection, and metronidazole and rifampicin were more effective in the treatment of fulminate gas gangrene caused by C. perfringens. Altın et al [25] found that metronidazole has identical in vitro effectiveness against anaerobic bacteria and it has exceptional in vitro activity against most strict anaerobic bacteria, such as clostridia, Bacteroides fragilis group, and other species of Bacteroides, and fusobacteria.…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…Stevens et al [24] demonstrated that the drugs were more active in the management of clostridial infection, and metronidazole and rifampicin were more effective in the treatment of fulminate gas gangrene caused by C. perfringens. Altın et al [25] found that metronidazole has identical in vitro effectiveness against anaerobic bacteria and it has exceptional in vitro activity against most strict anaerobic bacteria, such as clostridia, Bacteroides fragilis group, and other species of Bacteroides, and fusobacteria.…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…Recently, many cases have been reported with QT prolongation with/without TdP, in which metronidazole antibiotic had been used. Regardless of the medical history and the indication of metronidazole therapy either alone or in combination with other drugs, ECG reverted to normal within several hours of immediate drug withdrawal [8][9][10][11]. Likewise, a case had been reported in our clinic.…”
Section: Introductionmentioning
confidence: 99%